Sustained Progression-Free Survival Benefit of Rituximab Maintenance in Patients With Follicular Lymphoma: Long-Term Results of the PRIMA Study - Bachy, Emmanuel; Seymour, John F; Feugier, Pierre; Offner, Fritz; López-Guillermo, Armando; Belada, David; Xerri, Luc; Catalano, John V; Brice, Pauline; Lemonnier, François; Martin, Alejandro; Casasnovas, Olivier; et al. (Journal of clinical oncology, 2019)
PURPOSE: The PRIMA study (ClinicalTrials.gov identifier: NCT00140582) established that 2 years of rituximab maintenance after first-line immunochemotherapy significantly improved progression-free survival (PFS) in patients with follicular lymphoma compared with observation. Here, we report the final PFS and overall survival (OS) results from the PRIMA study after 9 years of follow-up and provide a final overview of safety. METHODS: Patients (> 18 years of age) with previously untreated high-tumor-burden follicular lymphoma were nonrandomly assigned to receive one of three immunochemotherapy induction regimens. Responding patients were randomly assigned (stratified by induction regimen, response to induction treatment, treatment center, and geographic region) 1:1 to receive 2 years of rituximab maintenance (375 mg/m2, once every 8 weeks), starting 8 weeks after the last induction treatment, or observation (no additional treatment). All patients in the extended follow-up provided their written informed consent (data cutoff: December 31, 2016). RESULTS: In total, 1,018 patients completed induction treatment and were randomly assigned to rituximab maintenance (n = 505) or observation (n = 513). Consent for the extended follow-up was provided by 607 patients (59.6%) of 1,018 (rituximab maintenance, n = 309; observation, n = 298). After data cutoff, median PFS was 10.5 years in the rituximab maintenance arm compared with 4.1 years in the observation arm (hazard ratio, 0.61; 95% CI, 0.52 to 0.73; P < .001). No OS difference was seen in patients randomly assigned to rituximab maintenance or observation (hazard ratio, 1.04; 95% CI, 0.77 to 1.40; P = .7948); 10-year OS estimates were approximately 80% in both study arms. No new safety signals were observed. CONCLUSION: Rituximab maintenance after induction immunochemotherapy provides a significant long-term PFS, but not OS, benefit over observation.
Keywords: Watchful Waiting; Humans; Antineoplastic Agents, Immunological; lidé středního věku; Disease Progression; Female; Aged; mladý dospělý; dospělí; Time Factors; senioři; lidé; doba přežití bez progrese choroby; časové faktory; Adult; ženské pohlaví; Male; rituximab; Middle Aged; Lymphoma, Follicular; Aged, 80 and over; pozorné vyčkávání; Rituximab; Young Adult; senioři nad 80 let; protinádorové látky imunologicky aktivní; progrese nemoci; Progression-Free Survival; mužské pohlaví; folikulární lymfom